EMPIRICAL MODEL COMPARISON AND MODEL TUNING FOR ESTIMATING a(CDOM) IN A TROPICAL RESERVOIR IN BRAZIL - Watanabe, Fernanda [UNESP]; Alcantara, Enner [UNESP]; Curtarelli, Marcelo; Nascimento, Renata; Stech, Jose; Kampel, Milton; IEEE (Ieee, 2015)
The aim of this work was to fit an empirical model for estimating the Colored Dissolved Organic Matter (CDOM) absorption coefficient (a(CDOM)) at 412 nm [a(CDOM)(412)] and 443 nm [a(CDOM)(443)], in Itumbiara reservoir (Goias State, Brazil). Two field surveys were carried out in May and September, 2009. Radiometric and water samples were collected and used to fit an aCDOM empirical model. Empirical models from literature were tested also and their performances were compared with the performance of fitted model.
Keywords: Remote sensing; tropical reservoir; a(CDOM); empirical models